2020
DOI: 10.1186/s13020-020-00336-8
|View full text |Cite
|
Sign up to set email alerts
|

Artesunate: could be an alternative drug to chloroquine in COVID-19 treatment?

Abstract: SARS (Severe Acute Respiratory Syndrome Coronavirus)-CV-2 (2019-nCov), which showed up in China in December 2019 and spread all over the world, has becomed a serious health problem. An effective, safe and proven treatment has not yet been found. Chloroquine has been recommended by some authors to be used for the treatment of patients infected with this virus however chloroquine may have side effects and drug resistance problems. Artesunate is a semisynthetic derivative of artemisinin, an antimalarial drug. Art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 39 publications
1
41
0
Order By: Relevance
“…In our analysis, we found that Artenimol or Artesunate, an alternative of Chloroquine could also be effective in treating COVID-19. Moreover, Artesunate was previously predicted to be a good candidate against SARS-CoV-2 [ 56 , 57 ] and is currently under clinical trial (NCT04387240).…”
Section: Discussionmentioning
confidence: 99%
“…In our analysis, we found that Artenimol or Artesunate, an alternative of Chloroquine could also be effective in treating COVID-19. Moreover, Artesunate was previously predicted to be a good candidate against SARS-CoV-2 [ 56 , 57 ] and is currently under clinical trial (NCT04387240).…”
Section: Discussionmentioning
confidence: 99%
“…In response to previous success stories in COVID-19 clinical case management in various parts of the world, the anti-malarial drugs chloroquine, hydroxychloroquine and artemisinin-based therapy have been widely used to treat the patients diagnosed with COVID-19 in addition to standard supportive care [ 13 , 14 ]. Reports of bulk procurement from foreign pharmaceutical companies and third-party wholesale distributors by the government or people in panic, have resulted in global shortage of anti-malarial drugs [ 15 ].…”
Section: Main Textmentioning
confidence: 99%
“…Artemisinin has a clinical impact potential in the treatment of COVID-19 because it can prevent the progression of the disease and accelerate the recovery of patients before they develop potentially life-threatening complications ( Uzun and Toptas, 2020 ; Krishna et al, 2021 ). This dual-function COVID-19 drug candidate is hoped to mitigate the cytokine-mediated inflammatory injury associated with the cytokine storm and viral sepsis in critically ill COVID-19 patients.…”
Section: Discussionmentioning
confidence: 99%